ESTIMATION OF CYTOMORPHOLOGICAL SPECTRUM OF THYROID LESIONS BY FINE-NEEDLE ASPIRATION CYTOLOGY BASED ON BETHESDA SYSTEM FOR REPORTING IN TERTIARY CARE HOSPITAL - REENA, NAIK; MEGHA, GAJENDRA; JYOTI, CHAUDHARY; CHAWDA, HANISH; MANOJ K, MINJ (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of this study were as follows: (1) To estimate thecytomorphological spectrum of thyroid lesions. (2) To categorize the thyroid lesions based on Bethesda system reporting. (3) To correlate the spectrum of thyroid lesions with demographic parameters. Methods: A retrospective record-based study was conducted at the Department of Pathology in Tertiary Care Institute, from January 2017 to January 2021. A total of 346 case files were retrieved consisting of all the patients having thyroid lesions who underwent the procedure of fine-needle aspiration cytology. Statistical analysis was done using the software Statistical Package for the Social Sciences (SPSS) 22.0 version. Continuous variables were presented by mean±SD and categorical variables by frequency or percentages. Results: Majority of the case are falling between the age group of 26–35 years, followed by 36–45 years of age. The majority of cases in the study population were presented with Bethesda Category II lesion (88.7%) which was found to be statistically significant (p<0.05), the most common spectrum was seen, which was Colloid nodule in 40.46% of cases categorized to Bethesda Class II. This was found to be statistically significant (p<0.05), followed by adenomatoid nodule in 30.92% of cases also Category II. Conclusion: Fine-needle aspiration cytology is a cost effective procedure that provides specific diagnosis rapidly with minimum complications.